The Effect of Amoxicillin-Clavulanate and Actifed Versus Actived Only in treatment of Otitis Media with Effusion - Muhei Rasheed, Ahmed; Hayder Taha, Yusra (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Otitis media with effusion(OME)is a common cause of deafness in children with subsequent impairment of speech development and scholastic difficulties.Treatmentremains controversial.Aim: To study the effect of amoxicillin-clavulanate in treatment of OMEPatients and methods: A prospective study of a target sample consisting of sixty children under the age of 12 years presented with chief complaints duration for at least 6 weeks andon examination there were bilateral red and retracted tympanic membranes without oversized adenoids and no underlying causes require surgical correction e.g cleft palate.Thepatients were divided into two groups;group A which received Actifed for 4 weeks and group B which received Actifed +Amoxicillin-clavulanate for 4 weeks treatmentcourse.After complete history and otolaryngological examination,all the patients were sent to x-ray of postnasal space( to exclude oversized adenoids),audiometry and tympanometry.Assessment was repeated at the end of 2 and 4 weeks of treatment course including audiometry and tympanometry.The response to treatment in group B wascompared to that in group A at the end of 4 weeks treatment course.In this study,we refered to improvement in otoscopic findings and tympanometry results to show the response to 4weeks treatment course.Results: Eight patients(25.81%)in group A have shown response to treatment at the end of 4 weeks treatment course,while the response in group B was seen in 15 patients( 51.72%).Conclusion: Amoxicillin-clavulanate has statistically significant effect in treatment of otitis media with effusion(OME)in short term follow-up and the clearance of middle ear efussionin response to amoxicillin-clavulanate indicates that bacterial infection may play a role in the aetiology of OME.